Evolution of microbial community structure during biohydrogen production process of palm oil anaerobic sludge - Akhbari A.; Awalin L.J.; Wen L.C.; Ali M.S.; Ibrahim S. (Elsevier Ltd, 2025)
Anaerobic microbial communities and their functions can provide information about waste management practices, as well as reveal novel degradation metabolisms that can be utilized in wastewater treatment. This study was aimed towards sustainable palm oil industry with assessing the microbial evolution during the dark fermentative processing of palm oil anaerobic sludge and palm oil mill effluent (POME) in batch-mode over two-months with a distinct incubation time of 24 h. The process was designed using response surface methodology (RSM) by acclimatization of inoculum using POME with a chemical oxygen demand (COD) of 36 g-COD/l. The effect of mesophilic and thermophilic conditions and pH on COD removal, hydrogen content, and hydrogen yield (HY) were investigated. A potential sample was selected for microbial analysis after the first and second months of operation based on the maximum outputs achieved throughout the experiment. The bacterial community at pH 5.6 and temperature 55 C with maximum hydrogen content of 64.13 %, and HY of 0.93 ml H2/g-COD was dominated by three phyla: Firmicutes, Actinobacteria, and Bacteroidota. The results obtained from high throughput pyrosequencing showed that how acclimatization period affects the microbial community structure towards Firmicutes phylum, which includes the majority of hydrogen-producing microorganisms. ? 2024 The Authors